EVALUATION OF ANTIFUNGAL POTENTIAL OF ALLIUM AMPELOPRASUM AGAINST FUNGAL PHYTOPATHOGENS - Khan, Shahid; Kaur, Amandeep; Sharma, Neeta Raj (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Present study evaluates the antifungal potential of Allium ampeloprasum extracts against two phytopathogens of economic importance, namely Alternaria triticina and Magnaporthe oryzae which are found to be one of the greatest threats to wheat and rice crop worldwide. Methods: Four different organic solvents, i.e., water, methanol, acetone, and hexane were used for extract preparation based on the increasing order of polarity. Further, different concentrations of these extracts were used to perform a quantitative assay for measuring the antifungal activity of extracts. Two-way analysis of variance was used to statistically analyze the results through GraphPad Prism v. 7.00. Results: The best results were shown by water extracts with a maximum inhibition of 99.39Â±0.2% against A. triticina and 99.39Â±2.2% against M. oryzae. Water extracts gave minimal inhibitory concentration 90 values at 9.94 Î¼g/mL against M. oryzae and at 16.73 Î¼g/mL against A. triticina. Conclusion: Water extracts of A. ampeloprasum have relatively higher potential for being used as an antifungal agent as compared to other organic extracts used in this study. Further study on the chemical composition of A. ampeloprasum water extracts can reveal potent anti-phytopathogenic fungal compounds which can be used to develop biofungicides.